Chirogenesis and Pfeiffer Effect in Optically Inactive EuIII and TbIII Tris(β-diketonate) Upon Intermolecular Chirality Transfer From Poly- and Monosaccharide Alkyl Esters and α-Pinene: Emerging Circularly Polarized Luminescence (CPL) and Circular Dichroism (CD) - Fujiki, Michiya; Wang, Laibing; Ogata, Nanami; Asanoma, Fumio; Okubo, Asuka; Okazaki, Shun; Kamite, Hiroki; Jalilah, Abd Jalil (Frontiers in Chemistry, 2020)
We report emerging circularly polarized luminescence (CPL) at 4f-4f transitions when lanthanide (EuIII and TbIII) tris(β-diketonate) embedded to cellulose triacetate (CTA), cellulose acetate butyrate (CABu), D-/L-glucose pentamethyl esters (D-/L-Glu), and D-/L-arabinose tetramethyl esters (D-/L-Ara) are in film states. Herein, 6,6,7,7,8,8,8-heptafluoro-2,2-dimethyl-3,5-octanedionate (fod) and 2,2,6,6-tetramethyl-3,5-heptanedione (dpm) were chosen as the β-diketonates. The glum value of Eu(fod)3 in CABu are +0.0671 at 593 nm (5D0→7F1) and –0.0059 at 613 nm (5D0→7F2), respectively, while those in CTA are +0.0463 and –0.0040 at these transitions, respectively. The glum value of Tb(fod)3 in CABu are –0.0029 at 490 nm (5D4→7F6), +0.0078 at 540 nm (5D4→7F5), and –0.0018 at 552 nm (5D4→7F5), respectively, while those in CTA are –0.0053, +0.0037, and –0.0059 at these transitions, respectively. D-/L-Glu and D-/L-Ara induced weaker glum values at 4f-4f transitions of Eu(fod)3, Tb(fod)3, and Tb(dpm)3. For comparison, Tb(dpm)3 in -pinene showed clear CPL characteristics, though Eu(dpm)3 did not. A surplus charge neutralization hypothesis was applied to the origin of attractive intermolecular interactions between the ligands and saccharides. This idea was supported from the concomitant opposite tendency in upfield 19F-NMR and downfield 1H-NMR chemical shifts of Eu(fod)3 and the opposite Mulliken charges between F-C bonds (fod) and H-C bonds (CTA and D-/L-Glu). An analysis of CPL excitation (CPLE) and CPL spectra suggests that (+)- and (–)-sign CPL signals of EuIII and TbIII at different 4f-4f transitions in the visible region are the same with the (+)-and (–)-sign exhibited by CPLE bands at high energy levels of EuIII and TbIII in the near-UV region.